Involvement of the ABCG37 transporter in secretion of scopoletin and derivatives by Arabidopsis roots in response to iron deficiency - Fourcroy, Pierre (The New phytologist, 2014)
© 2013 CNRS. New Phytologist © 2013 New Phytologist Trust.